"COVID Arm" in the family medicine setting: Moderna vaccine hypersensitivity reaction - Lara L Cohen; Antonio J Suarez; Bryan W Pardo (Wolters Kluwer Medknow Publications, 2022)
The Moderna COVID-19 vaccination has been widely distributed since authorized for emergency use. Phase 3 clinical trial data reported that 1.5% of recipients experienced hypersensitivity reactions after vaccination. The resulting erythematous rash, termed "COVID arm," has been described in isolated case reports. To our knowledge, existing literature has not presented this diagnosis in the family medicine setting. This study was exempt from Institutional Review Board approval. An 85-year-old female presented to our family medicine clinic with a rash at injection site 15 days after receiving the Moderna vaccine. She endorsed pruritus and allodynia. She was afebrile. The rash measured 8 cm (height) × 9 cm (width) and was erythematous, without edema or warmth. We determined the rash was a "COVID arm" hypersensitivity reaction. Family medicine physicians are newly responsible for providing education and care related to COVID-19 vaccination. This case provides a unique opportunity to review the suspected pathology of "COVID arm" and describe management in an outpatient setting. Patients without severe allergic reactions should proceed with the second dose in their other arm, anticipating possible repeat "COVID arm."